Prophets in the Holy Quran and the Torah (The Flood Story as an Example) (Journal of the College of Basic Education, 2025)
This study aims to present a comparative analysis of the concept of prophethood, the functions of prophets, and their characteristics in both the Holy Qur’an and the Old Testament. By examining sacred texts and analyzing the religious and intellectual contexts in which the concept of prophethood developed in Islam and Judaism, the research focuses on three main axes: the concept of prophethood, the role of the prophet, and his attributes. The study reveals that prophethood in the Qur’an is rooted in monotheism, infallibility, and divine selection. Prophets in Islam are portrayed as morally and spiritually exemplary figures who are held in the highest esteem. In contrast, the Old Testament presents prophethood in a historical and nationalistic framework, where prophets are often depicted in the context of political and social events related to the people of Israel, and may be attributed actions that conflict with the Islamic view of prophetic infallibility The research concludes that both scriptures agree on the divine purpose of prophethood as a means to guide humanity, yet they differ fundamentally in their portrayal of prophets, their conduct, and the objectives of their missions. The Qur’an employs prophetic stories for spiritual and moral reform, while the Torah frames them as part of Israel’s historical narrative This study contributes to a deeper comparative understanding between religions and underscores the importance of critically and academically studying shared concepts to promote interfaith and cultural dialogue